2018
DOI: 10.1098/rsos.171024
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of the Viking Age in Ireland as portrayed inCogadh Gaedhel re Gallaibh

Abstract: Cogadh Gaedhel re Gallaibh (‘The War of the Gaedhil with the Gaill’) is a medieval Irish text, telling how an army under the leadership of Brian Boru challenged Viking invaders and their allies in Ireland, culminating with the Battle of Clontarf in 1014. Brian’s victory is widely remembered for breaking Viking power in Ireland, although much modern scholarship disputes traditional perceptions. Instead of an international conflict between Irish and Viking, interpretations based on revisionist scholarship consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In the case of character networks, edge signs represent antagonistic relationships, generally friendly vs. hostile [63,151,157,175]. Mac Carron et al [154,155,157,277] study the number of imbalanced triangles in their mythological networks, and the low proportion they find is comparable with what is generally observed in real-world social networks. Sack [214][215][216] studies the evolution of the network balance, a quantity related to the number of balanced triangles it contains, to identify several phases in the plot (progress towards stability, reversal, factions formation, resolution...).…”
Section: /75mentioning
confidence: 97%
“…In the case of character networks, edge signs represent antagonistic relationships, generally friendly vs. hostile [63,151,157,175]. Mac Carron et al [154,155,157,277] study the number of imbalanced triangles in their mythological networks, and the low proportion they find is comparable with what is generally observed in real-world social networks. Sack [214][215][216] studies the evolution of the network balance, a quantity related to the number of balanced triangles it contains, to identify several phases in the plot (progress towards stability, reversal, factions formation, resolution...).…”
Section: /75mentioning
confidence: 97%
“…The prevalence of various HLA alleles varies widely in different populations. Although the British, Irish and Scandinavian populations are now culturally distinct and geographically separate from each other, there are historical reasons dating back to centuries to suggest that some of their key genetic features overlap . The inevitable question is whether the three populations also share parts of their HLA allelic profile and, therefore, the high risk of dipyrone‐induced agranulocytosis; one study has already reported a high incidence of this complication in Sweden at one case per 1439 prescriptions .…”
Section: Commentmentioning
confidence: 99%
“…Much of the work of historians in this area tries to reconstruct 'real' social networks, based on data from a variety of sources, to understand the power of communities in the past [7]. This article, by contrast, builds on recent studies of character networks in narratives, fictional or otherwise, which seek to reconstruct how individual texts or sets of texts present the connections between actors they describe, and with what results [8][9][10][11]. A benefit of the study of character networks is that it not only allows us to unveil complex hidden structures in past societies, as network science generally does, but to reveal unspoken principles underlying the representation of human relationships through investigation of who the authors of these texts connected with whom.…”
Section: Introductionmentioning
confidence: 99%